Analysis of errors and prevention of complications after perosseous osteosynthesis - Bodnya, A.; Butenko, L.; Vadatursky, M. (Journal of Education, Health and Sport, 2021)
Distal fractures rank a special place among all fractures of the long tubular bones of the extremities. Complications are an inevitable companion of any surgical intervention, as well as an integral part of the work of every surgeon. Objective: To analyze the outcomes of treatment of distal fractures of the long bones of the extremities, to identify the causes of errors and the frequency of complications after perosseous osteosynthesis, and to outline ways for their prevention. Patients and methods: 1723 patients with distal fractures of the long bones of the extremities and further perosseous osteosynthesis have been under study. Distal fractures of the humerus were registered in 647 patients, those of the femur – in 392, and the bones of the lower leg were damaged in 684. Results: The most common complication of perosseous osteosynthesis is inflammation of the soft tissues near the pins - 21.8%. Non-infectious complications (secondary displacement of fragments, contractures, impaired innervation and trophism) were observed in 18.2% of cases. Residual effects of neuritis of the radial and peroneal nerves amounted to 0.1%. In the long-term period there were 2.1% of the knee and elbow joints contractures. Conclusions: Complications observed in the process of treatment of distal fractures of long bones of the extremities with the use of perosseous osteosynthesis are not inherent this method of treatment, since they are the result of medical errors in the choice of indications for its use, violations of osteosynthesis’ technique and postoperative management of patients, mainly in the period of minimally invasive technology of surgical intervention development.